Studies on the shootborer Hypsipyla grandella (Zeller) (Lepidoptera Pyralidae). V. Observations on a rearing technique and on host selection behavior of adults in captivity - Grijpma, P. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
A technique for the laboratory rearing of Hypsipyla grandella Zeller and a method for the mass production of the insect's eggs are described. Based on the data observed with two types of diets, one synthetic and one natural, an equation was estimated that governs the pupal stage and emergence as a function of time. Of three distributions tested (Poisson, normal, and binomial), the binomial best fit the observed data. The generations of H. grandella adults raised on a synthetic diet and under the experimental conditions continued to lay eggs on Cedrela odorata plants. It was found that the adults raised on a synthetic diet were larger than the adults raised on a natural diet of leaves and tender shoots of C. odorata. The size of the female H. grandella raised on both types of diets was significantly larger than that of the male. Females raised on both diets lived longer than the males Adults of H. grandella raised on a natural diet were found to be attacked at night by light from a light bulb and by pupae or dried leaves of C. odorata. A response model is suggested for a series of stimuli that could cause H. grandella selectivity for Meliaceae.